Work experience, work stress and HRM at the university - Liebeth Adriaenssens; Peggy De Prins; Daniël Vloeberghs (Management Revue, 2006)
Current research on stress among academic university staff indicates that occupational stress is alarmingly widespread and increasing (Kinman/Jones 2004; Winefield et al. 2003; Bamps 2004; Tytherleigh et al. 2005). Therefore the work environment needs to be examined and more specifically organisational specific characteristics, like HRpractices. In line of Timmerhuis (1998), we believe that management of human resources in the academic sector is very useful and necessary. The aim of our study is to investigate (1) the well-being (job stress and job dissatisfaction) of academic staff at the University of Antwerp, (2) the specific factors of the work environment who have an impact on employee well-being, and (3) the interaction between HR practices and employee well-being. (4) Finally, suggestions of improvement of the work environment are to be formulated. In order to meet this purpose, we designed a conceptual model, based on the stress model developed in the Institute for Social Research (ISR) (University of Michigan), and on the HR-model of Peccei (2004). Central to the model is the idea that employee satisfaction and stress are a function of the subjective perception of the work environment which, in turn, is affected by the HR practices that are in place in organisations. The elements most likely to cause job stress, according to our participants, were workload and time pressures, uncertainty, lack of feedback and social support. Further, it appeared that the HR-related job characteristics cause job dissatisfaction: perceptions on participation, assessment, reward and support have an impact on job satisfaction of the academic staff. Finally, suggestions of improvement of the work environment were mentioned.
Keywords: 650; employee well-being; Human Resource Management; universities; job stress; Personalmanagement; Arbeitszufriedenheit; Stress; Hochschule; Belgien